Kinetochore Architecture Employs Diverse Linker Strategies Across Evolution - Sridhar, Shreyas; Fukagawa, Tatsuo (Frontiers in Cell and Developmental Biology, 2022)
The assembly of a functional kinetochore on centromeric chromatin is necessary to connect chromosomes to the mitotic spindle, ensuring accurate chromosome segregation. This connecting function of the kinetochore presents multiple internal and external structural challenges. A microtubule interacting outer kinetochore and centromeric chromatin interacting inner kinetochore effectively confront forces from the external spindle and centromere, respectively. While internally, special inner kinetochore proteins, defined as ‘linkers’, simultaneously interact with centromeric chromatin and the outer kinetochore to enable an association with the mitotic spindle. With the ability to simultaneously interact with outer kinetochore components and centromeric chromatin, linker proteins such as centromere protein (CENP)-C or CENP-T in vertebrates and, additionally CENP-QOkp1-UAme1 in yeasts, also perform the function of force propagation within the kinetochore. Recent efforts have revealed an array of linker pathways strategies to effectively recruit the largely conserved outer kinetochore. In this review, we examine these linkages used to propagate force and recruit the outer kinetochore across evolution. Further, we look at their known regulatory pathways and implications on kinetochore structural diversity and plasticity.